Comparison of Effects of Low Level Laser and Ultrasound Therapy in Plantar Fasciitis - Malik, Aiesha; Saima Riaz; Mehmood, Fatima; Zeeshan, Muhammad; Muhammad Zeshan Ahmad (International Journal of Innovative Research in Medical Science, 2020)
Plantar Fasciitis is among the major causes of heel pain. Mechanical stress of plantar aponeurosis usually causes inflammation thus result in problem with weight bearing and difficulty in walking. Pain often exacerbates and may stick at for months with unremitting activity, limiting the activities of daily living and the functional status. The objective of the study was to compare the effects of low level laser and ultrasound therapy in patients for pain and their functional status presents with plantar fasciitis. This study was a Quasi-experimental trial and conducted at Physical therapy Center for Arthritis & Rehabilitation Excellence (PT CARE), Gulberg III Lahore. The study completed in the time duration of six months (Aug 2019 – Jan 2020). Consecutive sampling technique was used to collect the data. A sample size of `total 28 patients were taken in this study; patients were divided into two groups. Conventional Physiotherapy protocol was given to both groups as baseline treatment. (Group A patients were treated with low level laser protocol whereas Group B was treated with ultrasound therapy protocol). Functional Foot Index (FFI) score was used to ask some questions related to patients symptoms and daily activities and to measure the intensity of pain Numeric Pain Rating Scale (NPRS) was used. All participants of the study filled the FFI & NPRS score and Numeric pain rating scale on day 1 in first cycle as pretreatment values and at the end of 5th session and 10th session as first and second cycles as post treatment values respectively. Data was analyzed on SPSS 21.The means of pre-treatment NPRS in group A was 7.78 and in group B means of pre-treatment NPRS was 7.35 with p value <0.05. Means difference of NPRS for group A was 4.07 and in group B the post treatment-1 means difference 4.85 with p value <0.05. Means of post treatment-2 in group A was 1.71 and in group B was 2.64 with p value <0.05. While means of pre-treatment in group A for FFI was 77.66 in group A and group B was 73.35 with p value <0.05. Means of post treatment-1 for group A for FFI was 54.50 and for group B 58.27 with p value <0.05. And means of post treatment-2 in FFI for group-A was 28.22 and for group B was 35.88 with p values <0.05. Low Level Laser Therapy is more effective than Ultrasound Therapy in reducing pain and improving functions in patients with plantar fasciitis and vice versa.